Exploring EFL Students’ Engagement and Learning Outcomes through AO3 Fanfiction: A Descriptive Study at SMAN 1 Tenggarong - Aji Evita Hanifa; Khusnul Khatimah; Ade Ismail Ramadhan Hamid (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores the influence of reading fanfiction on the Archive of Our Own (AO3) platform on students’ engagement with English narrative texts and the perceived learning benefits for English as a Foreign Language (EFL) learners. Conducted at SMAN 1 Tenggarong, East Kalimantan, the study involved 38 high school students who actively engage with fanfiction on AO3. Using a quantitative approach, data were collected through a 14-item online questionnaire and analyzed using SPSS version 26 for reliability, validity, and descriptive statistics. The findings reveal that students showed high motivation when reading content that matched their interests (M = 4.29, SD = 0.93) and reported a preference for fanfiction over textbooks (M = 3.32). Students said they enjoyed reading (M = 3.03), relevance of content (M = 3.18), and platform usability (M = 3.26) as moderate. Regarding learning outcomes, students perceived notable benefits in vocabulary development (M = 3.40) and interest in reading English (M = 3.42), while grammar exposure (M = 3.11) and confidence in reading (M = 3.08) received moderate ratings. Gender-based analysis showed that male students had slightly higher engagement, while female students reported greater gains in vocabulary and interest. These results suggest that AO3 fanfiction serves as an engaging and effective supplementary tool for EFL learners, particularly in fostering vocabulary growth, reading motivation, and reader autonomy. While it may not fully replace structured grammar instruction, its personalized and enjoyable content can enhance student interaction with English texts and promote a more meaningful reading experience in digital environments.